USE OF COMPLEMENTARY AND ALTERNATIVE MEDICINE AMONG ASTHMATIC PATIENTS - Ahmed, Fawad; Ayub, Ayaz; Hussain, Hamid (Journal of Ayub Medical College Abbottabad, 2017)
Background: The prevalence of complementary and alternative medicine (CAM) use in some developed countries is on the rise as surveys conducted on large scale vouch for. This study was conducted with the aim to determine the frequency of complementary and alternative medicine (CAM) use among asthmatic patients at outpatient department of tertiary care hospitals in Peshawar, Khyber Pakhtunkhwa, Pakistan. Methods: This cross-sectional study was conducted in outpatient department of two tertiary care hospitals. A face to face interview of 423 patients was conducted through a questionnaire. Non-probability consecutive sampling method was used to select the respondents. Stata version 12.1 (StataCorp), College Station, Texas) was used to carry out the statistical analysis. Results: Overall asthmatic patients in the study were 423, in which 232 (54.85%) patients reported as using CAM. There were 177 (41.84%) males and 246 (58.16%) females. The CAM use was significantly more in older age patients, suffering from asthma for more than 5 years, severe persistent type of asthma, married, unemployed, rural and current smokers. Conclusion: The use of CAM reflects a high CAM use among asthmatic patients in Pakistan. Clinicians should be aware about their patient’s use of CAM. Keywords: Complementary and alternative medicine; Asthma, patients; Pakistan